Factors that Affect Consumers to Buy Medicine from E-Pharmacy - Sachin Kumar Phogat, Vipul Dayma (International Journal of Advanced Science and Technology, 2020)
Internet is a boon to every individual in this world, with over 556 million people in India using the internet and organization also leveraging it by providing services through an online channel. The same is true for pharmacy, providing medicine and other related health services to the consumers. Through this research paper we try and understand which all factors that influenced consumer to buy medicine from e-pharmacy overall and amongst different age groups. The study is conducted on different independent parameters, which includes cost of medicine, medicine usage awareness, availability of medicine, quality of medicine and safety of information, and which independent parameter will be consider more by a particular age group and factors that are prominent in all. The survey consists of several questions on all these parameters and is conducted online, where around 109 respondents have responded to it and out of that 6 respondent’s data is not filled completely. So, total of 103 respondents were used for the study. The statistical technique that we have used is correlation and regression. Although there are various independent variables which are correlated with the buying intention individually for different groups, but the two factors that are prominent in all the consumers (independent variable significantly associated with dependent variable) amongst different group are Fake/Counterfeit medicine and Safety of information, means no age group would like to compromise on the part of quality and also consumers now a days would like to safe their personal data on the web portal. Also, from our study it can conclude that people with the age less than 35 shows positive response towards medicine from e-pharmacy, and people above that age are still not sure whether they would like to buy medicine from e-pharmacy, they are neutral towards buying from e-pharmacy and wanted to continue with the route of buying medicine through retail chemist/offline channel.